Revitalisasi Pembelajaran Matematika : Pembagian Lewat Permainan Tradisional Congklak di Kelas 4 MI Salafiyah Dadirejo - Atiyah Atiyah (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to investigate how the traditional game of Congklak is used in teaching the concept of division in the 4th-grade mathematics class at MI Salafiyah Dadirejo. Mathematics is often considered difficult and uninteresting by students, especially division, which can be quite challenging to understand. Therefore, creative teaching methods are needed to enhance students' understanding. As a more interactive and enjoyable tool for teaching division, the traditional game of Congklak, which is known in various regions of Indonesia, is introduced. This study uses a qualitative research method with a case study approach at MI Salafiyah Dadirejo. Data collection methods include observation, interviews, and documentation. The results of the study show that integrating the Congklak game into the learning process helps students better understand the concept of division. In addition to improving students' understanding of division, this game also enhances their social skills and increases their participation in the classroom. Traditional games like Congklak, which offer a more tangible and direct approach to learning, are a great alternative for teaching mathematics, especially concepts that require more practical understanding. These findings highlight the potential of using traditional games in modern education to create engaging and effective learning experiences for students.